Effect of chemical treatments of arundo donax L. fibre on mechanical and thermal properties of the PLA/PP blend composite filament for FDM 3D printing - Tablit, Sarra; Krache, Rachida; Amroune, Salah; Jawaid, Mohammad; Hachaichi, Amina; Ismail, Ahmad Safwan; Meraj, Aatikah (Elsevier, 2024)
Arundo donax L. is investigated in this study as a suitable reinforcing agent for PLA/PP waste blend 3D printing filament. To improve the compatibility of the fibre and polymer, the Arundo fibre was chemically modified using alkali and silane treatment. Untreated and treated fibres were extruded with Polymer blends before being 3D printed. Effect of chemical treatment on thermal, mechanical, and morphological properties of the composites was investigated. The tensile, Izod impact, and water absorption of the 3D printed specimens were also tested. The Alkali treated (ALK) and combination of alkali and silane treatment (SLN) composites displayed good results. Tensile strength and modulus of the materials increased, as well as their maintained stability in the Izod impact test, demonstrating that the incorporation of ArF did not result in a loss in performance. SEM examination supported these findings by confirming the creation of beneficial interfacial contacts between the matrix and fibre components, as demonstrated by the lack of void between the matrix and the fibre surface. Furthermore, the alkali treatment of the ArF resulted in a considerable reduction in water absorption inside the biocomposite, with a 64 reduction seen in ALK composite comparison to the untreated composite (Un). After the 43-day assessment period.